2010
DOI: 10.1021/jm101252m
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Stability and Intracellular Accumulation of Quercetin by Protection of the Chemically or Metabolically Susceptible Hydroxyl Groups with a Pivaloxymethyl (POM) Promoiety

Abstract: In order to increase stability of quercetin, its metabolically and chemically susceptible hydroxyl groups 7-OH and 3-OH respectively were transiently blocked with a pivaloxymethyl (POM) promoiety to provide two novel quercetin conjugates [7-O-POM-Q, 3-O-POM-Q]. In the absence of stabilizer (ascorbic acid), the synthesized conjugates showed significantly increased stability in cell culture media [t(½) = 4 h, 52 h] compared with quercetin (t(½) < 30 min) and quercetin prodrug 1 (t(½) = 0.8 h). In addition, the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 70 publications
0
40
0
Order By: Relevance
“…There is also a need to address the issue of the low bioavailability of quercetin especially for therapeutic use [29][30][31]. Several strategies to increase the bioavailability of quercetin that include using lipids and emulsifiers, co-crystalization of quercetin or using ester-based precursors have been investigated [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…There is also a need to address the issue of the low bioavailability of quercetin especially for therapeutic use [29][30][31]. Several strategies to increase the bioavailability of quercetin that include using lipids and emulsifiers, co-crystalization of quercetin or using ester-based precursors have been investigated [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…6C and D). This is not surprising because quercetin or its metabolite levels in the cells peak at 5 h post treatment and it is slowly reduced with time and completely depleted by 24 h (Kim et al, 2009(Kim et al, , 2010a. Therefore addition of quercetin during or immediately after viral infection may be necessary to effectively limit viral infection in vitro.…”
Section: Presence Of Quercetin During Rv Infection Is Necessary To LImentioning
confidence: 99%
“…Zhang et al (2011) reported that a hydroxypropyl-β-cyclodextrin-genipin complex increased water solubility 3.5-fold. Chemical modification of flavonoids with a pivaloxymethyl group is another method (Kim et al, 2010). However, these methods also have drawbacks, including compromised product purity, difficulty of preparation, and environmental pollution.…”
Section: Introductionmentioning
confidence: 99%